Advances in research on propofol-induced postoperative cognitive dysfunction via Piezo channels - Xue, Han; Zhang, Xiaoyu; Chou, Chenxu; Jia, Yulong; Hao, Chunguang; Duan, Xiaguang (Frontiers in Molecular Neuroscience, 2025)
Postoperative cognitive dysfunction (POCD), which often affects elderly patients after anesthesia and surgery, is characterized by memory loss, trouble concentrating, and difficulties with thinking and decision-making. Propofol is a commonly used intravenous anesthetic. Its effects on the brain are complex, and researchers have been paying closer attention to them. While it can protect nerve cells in some situations, it may also cause damage. Emerging evidence suggests that mechanosensitive Piezo ion channels may serve as critical mediators. These channels allow cells to detect mechanical forces and turn them into biological signals. They may act as a link between propofol use and cognitive decline. This review highlights new findings on how propofol may affect Piezo channel function. It shows that propofol changes the physical properties of cell membranes. It makes the membranes stiffer and less fluid. These changes may change how Piezo channels react to mechanical forces. They can disturb calcium signals and synaptic function in the brain. This problem can increase inflammation and damage to mitochondria. It can weaken synaptic connections and cause cognitive decline, especially in older adults. Additionally, calcium entering through Piezo1 channels has been linked to inflammation, which may be another mechanism by which propofol and Piezo channels together cause POCD. However, clear proof of how propofol interacts with Piezo channels is still lacking. More research with molecular simulations, genetic models, and calcium imaging is needed to better understand these processes.